EFFECTS OF LOCAL DIFFERENCE FEEDER FOR PERFORMANCE PRODUCTION OF LAYER PHASE QUAIL PADJADJARAN ABSTRACT - Juliani, Silvi (Jurnal Produksi Ternak Terapan, 2025)
Good maintenance management can affect productivity and performance. This study aims to find out the impact of different feeders on the performance of the quail layer phase. The research was conducted from January 27 to February 26, 2024, located at the Breeding Center Puyuh, Faculty of Agriculture, Padjajaran University. The objects used in this study are 180 Puyuh Padjadjaran females of selected black rodents who are eight weeks old. The cages are divided evenly into 18 cages, each of which is filled with 10 cages. The study used an experimental method with a complete random design (RAL) with 3 treatments consisting of P1 (artupic feeder), P2 (rough feeder), and P3 (through feeders with holes), with each treatment performed 6 repetitions. The data was tested using an ANOVA with a Duncan double-distance test. The observed parameters were feed intake, egg production, and feed conversion ratio. The results of the study showed that the treatment of different feeders had an influence on rant consumption of about 815,44 grams and egg production of about 92.80%, but had an unrealistic effect on the conversion of ransoms of layer-phase quail.